On Phraseologisms such as losing mind Type of Semantics and Useage - Kudirka, Robertas (Respectus Philologicus, 2001)
In colloquial speech the phrase važiuoja stogas doesn ’t contradict the system of Lithuanian language; thus, the phrase can be used as a figurative meaning of "losing mind."